Analisis Tingkat Kepuasan Pengguna Terhadap Penerapan Rekam Medis Elektronik (RME) di RS PKU Muhammadiyah Karanganyar - Adelia Cahya Utami; Muhlizardy Muhlizardy (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: By 2022 it will be found that 50% of the 3000 hospitals in Indonesia will have implemented electronic medical records. Of this percentage, only 16% have properly maintained electronic medical records. One of them is PKU Muhammadiyah Karanganyar Hospital implementing Electronic Medical Records (RME) in 2023 and it has only been fully implemented in the outpatient polyclinic section. For inpatient treatment, PKU Muhammadiyah Hospital still uses manual. The objective of the research: to determine the level of user satisfaction with the implementation of Electronic Medical Records (RME) at PKU Muhammadiyah Karanganyar Hospital. Method: This type of research is quantitative descriptive using a cross-sectional approach. Results: the level of satisfaction of Electronic Medical Record (RME) users was 51.2% of respondents who felt satisfied seen in the 5 dimensions of EUCS (End User Computing Satisfaction). The results obtained were that respondents felt satisfied (score 3.26) that the content was included in the category satisfied (3.41), accuracy (accuracy) is in the satisfied category (3.22), format (display) is in the satisfied category (3.16), ease of use is in the satisfied category (3.24 ), and timeless (punctuality) are in the satisfied category (3.27). Conclusion: the electronic medical record (RME) at PKU Muhammadiyah Karanganyar Hospital is running well and meets user expectations, especially in 5 aspects, namely content, accuracy, format, ease of use, and timeless.